Pembelajaran Bahasa Inggris Untuk Para Siswa Sekolah Dasar Di Rumah Belajar Sosial - Maria G Sri Ningsih; Noni Mia Rahmawati (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
The implementation of community service aimed at improving the English proficiency of the students in study house. The methods applied in this training were the provision of materials and practice. The provision of materials was the provision of guidance and explanation of the theory of English. After that, the teacher gave the questions and asked the students to do and practice dialogue in English. There were two study houses namely home study in Sido Rahayu and in Pandan Landung. The results of the activities were: at Sido Rahayu home study: 100% students always came and followed the activities held twice a week. 90% students understood the material and could work on the questions given by the teacher in writing. 80% students could do independently and could do a conversation.At Pandan Landung home study: 100% students always actively came. 75% students really understood the material and could work on the questions in writing. 6o% students could do independently the problems given by teachers and could do a simple conversation.